PARADIGMA DALAM KEBIJAKAN DESENTRALISASI DI INDONESIA: SEBUAH KRITIK TERHADAP DOMINASI PUBLIC ADMINISTRATION SCHOOL - Tirtosudarmo, Riwanto (Jurnal Masyarakat dan Budaya, 2008)
In this article, the underlying approach that has been used to formulate the post-Soeharto's territorial reform that produced decentralization laws and regulations is critically reviewed. The so-called Public Administration School or "PAS" that is rooted on the formal-legal paradigm and adopted by the discipline of law and political sciences has dominated the thinking behind the formulation of the decentralization and regional autonomy laws. The legal drafter of the decentralization laws in Indonesia are strongly influenced by the PAS approach and have crafted a national law that is generally lack of comprehensive understanding on the dynamics and processes at the society level. The PAS approach is failed in their attempt to incorporating various dimensions that are not only formatted but also contextualized the society. The critical implications that are mostly beyond the imagination of the experts that belong to the PAS approach is the fact that the news have created many loopholes for political elites to easily manipulating the existing regulations for their short term goal to capture the regional political positions and economic benefits. Two case studies of "pemekaran wilayah" in Central and Southeast Sulawesi provinces are presented to show the actual processes in which “pemekaran” become an arena for the local elites to contest for power and economic resources. A more comprehensive approach that is able to incorporating social, economic and ecological dimensions is needed to avoid the flaws, hypocrisy and manipulation by the political elites, as we have noticed in the implementation of the current decentralization laws and government regulations.